Surviving acute cyanide poisoning: a longitudinal neuropsychological investigation with interval MRI. (19th March 2014) - Mohan, Adith; Lee, Teresa; Sachdev, Perminder
Abstract : We report the case of a 22-year-old woman who presented with self-poisoning by cyanide ingestion. We have elected to pay particular attention to describing the neuropsychological sequelae of cyanide poisoning, and the evolution of these deficits over a 6-month period. Prominent deficits in episodic memory were noted from an early stage, which were consistent with the findings noted on structural neuroimaging. These deficits remained persistent, although improving in severity over the follow-up period. No focal neurological deficits or abnormal involuntary movements emerged, and the patient's overall functional status remained satisfactory. The patient's psychiatric presentation and background history are briefly discussed.